Arquitetura da informação para publicação de dados abertos conectados - Brandt, Mariana Baptista [UNESP]; Vidotti, Silvana Aparecida Borseti Gregorio [UNESP] (IBICT, 2024)
Publication of linked open data is not widespread, preventing the web from reaching its full potential. Thus, the objective is to propose structuring the data directly in the information systems in which they are generated, through the inclusion of a step for representing the business metadata in RDF format, in the methodology of information architecture for business processes (AIPN). An analysis of the literature and documentation of the W3C was carried out, in addition to applied research. It was observed that there are analogous elements between the RDF structure and the AIPN, which enables the inclusion of a semantic structure in the production of data through an RDF description step of the business metadata.